A Qualitative Inquiry into Nursing Students’ Experience of Facilitating Reflection in Clinical Setting - Shahnaz Karimi; Fariba Haghani; Nikoo Yamani; Majid Najafi Kalyani (The Scientific World Journal)
Background and Aim. Reflection is known as a skill that is central to nursing students’ professional development. Due to the importance and the role of reflection in clinical areas of nursing, it is important to know how to achieve it. However, nursing trainers face the challenge of how to help their students to improve reflection in clinical settings. The aim of this study was to investigate the nursing students’ experiences of facilitating reflection during clinical practice. This qualitative study was conducted by qualitative content analysis approach. Twenty nursing students during the second to eighth semester of their educational program were selected for participation using purposive sampling. Data were collected through in-depth semistructured interviews. The interview was transcribed verbatim, and qualitative content analysis was used to analyze the data. From the data analysis, four main themes were extracted. Motivation to reflect, complex experiences, efficient trainer, and effective relations were four main themes obtained from study that, in interaction with each other, had facilitating roles in students’ reflective process on experiences. The findings revealed that the nursing students’ reflection in clinical settings is effective in personal and professional level. Reflection of nursing students depends on motivational and educational factors and these factors increase the quality of care in patients. Furthermore, nursing educators need to create nurturing climate as well as supporting reflective behaviors of nursing students.